Transverse modulation of the positron beam density by using the laser standing wave; Journal of Physics: Conference Series; Vol. 732 : Radiation from Relativistic Electrons in Periodic Structures (RREPS2015) - Babaev A. A. Anton Anatoljevich (General Aspects of Physical Phenomena and Processes Associated with Electromagnetic Radiation, 2016)
Title screen